Non-Invasive and Minimum Invasive Concepts in Prevention, Cariology and Endodontics – from Research and Science to Practice - Boteva Ekaterina (Sciendo, 2018)
The minimum invasive dental concept is based on practical experience of more than 30 years negative trends from the use of resin materials in distal teeth and early metal-ceramic “aesthetic” crowns and bridges. The scientific dental research includes all aspects of the conservative dentistry treatment which are scientifically and clinically proved with most up to date methods and tests: anthropometric, epidemiological, biochemical, immunohistochemical, electron microscopy, polarized light microscopy, light induced fluorescence, microradiography, microbiology, genetic tests, etc. Experiments in vitro, animal tests, clinical research in the last 34 years are focused in the field of prevention of dental caries, treatment of precavitated precarious lesions with nanotechnologies, preparation of hard dental tissues with most conservative techniques, adhesive restoration methods with amalgam and resins, backup in endodontics in root canals preparation methods and in pins and posts fixations. The conclusions can be focused on basic principles and refocused in the 21st century like: Dental caries is not only predictable and controlled disease but is also a polyetiological disease on a community and population levels and uni- or bi-etiological on an individual level. The minimum invasive dental concept in cariology and endodontics leads to prevention of early extractions, early prosthetic medical procedures and to lifetime dental health. This plays a key role in prevention of metabolic disorders and gastrointestinal diseases.